2017
DOI: 10.1155/2017/8967902
|View full text |Cite
|
Sign up to set email alerts
|

Box-Counting Method of 2D Neuronal Image: Method Modification and Quantitative Analysis Demonstrated on Images from the Monkey and Human Brain

Abstract: This study calls attention to the difference between traditional box-counting method and its modification. The appropriate scaling factor, influence on image size and resolution, and image rotation, as well as different image presentation, are showed on the sample of asymmetrical neurons from the monkey dentate nucleus. The standard BC method and its modification were evaluated on the sample of 2D neuronal images from the human neostriatum. In addition, three box dimensions (which estimate the space-filling pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…The fractal analysis of the retinal vascular network was performed using the box-counting method (Smith et al, 1996 ; Fernández and Jelinek, 2001 ; Milošević, 2015 , 2016 ; Rajkovic et al, 2017 ). The RFI images were imported in Image J (National Institutes of Health, Bethesda, MD) and used to calculate the FD after grayscale format conversion (Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The fractal analysis of the retinal vascular network was performed using the box-counting method (Smith et al, 1996 ; Fernández and Jelinek, 2001 ; Milošević, 2015 , 2016 ; Rajkovic et al, 2017 ). The RFI images were imported in Image J (National Institutes of Health, Bethesda, MD) and used to calculate the FD after grayscale format conversion (Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Then, we investigated whether there is a connection between two parameters of the monofractal [13] and the GLCM analysis [15]. We have shown that even though these parameters describe different image properties, there is a correlation between them (Figure 2).…”
Section: Computational Analysismentioning
confidence: 99%
“…Among various methods of computational analysis, the monofractal analysis appears to be the method which suitably computes natural objects, when they can be characterized with the unique value of the fractal dimension [13,19]. On the contrary, when objects possess an uneven distribution of complexity, with fractal dimension fluctuating from point to point within an object [20], then a multifractal analysis is appropriate.…”
Section: Quantification Of the Binary Imagementioning
confidence: 99%
See 2 more Smart Citations